Telescopic Partial Dentures-Concealed Technology - Bhagat, Tushar Vitthalrao (J Int Oral Health, 2015)
The ideal goal of good dentist is to restore the missing part of oral structure, phonetics, his look and the most important is restored the normal health of the patient, which is hampered due to less or insufficient intake of food. Removable partial denture (RPD) treatment option is considered as a notion, which precludes the inevitability of “floating plastic” in edentulous mouth, that many times fail to fulfill the above essential of the patients. In modern dentistry, though the dental implants or fixed partial denture is the better options, but they have certain limitations. However, overdentures and particularly telescopic denture is the overlooked technology in dentistry that would be a boon for such needy patients. Telescopic denture is especially indicated in the distal edentulous area with minimum two teeth bilaterally present with a good amount of periodontal support. This treatment modality is sort of preventive prosthodontics remedy, which in a conservative manner preserve the remaining teeth and helps in conservation of alveolar bone ultimately. There are two tenets related to this option, one is constant conservation edentulous ridge around the retained tooth and the most important is the endless existence of periodontal sensory action that directs and monitor gnathodynamic task. In this option the primary coping or inner coping are cemented on the prepared tooth, and a similar removable outer or inner telescopic crown placed tightly by using a mechanism of tenso-friction, this is firmly attached to a removable RPD in place without moving or rocking of the prosthesis, which is the common compliant of almost all patients of RPD. Copings are also protecting the abutment from tooth decay and also offers stabilization and maintaining of the outer crown. The outer crown engages the inner coping and gives as an anchor for the remainder of the dentition. This work is the review of telescopic prosthesis which is well supported by the case discussion, and designates the utilization of favorable retained tooth/teeth as abutment that drastically minimized alveolar bone resorption beneath the prosthesis and give the maximum tactile sensation of natural teeth to the patient, which is not possible with other type of RPD.